2019
DOI: 10.1111/jocn.14774
|View full text |Cite
|
Sign up to set email alerts
|

The practice of glycaemic control in intensive care units: A multicentre survey of nursing and medical professionals

Abstract: Aims and objectives To determine the views of nurses and physicians working in intensive care units (ICU) about the aims of glycaemic control and use of their protocols. Background Evidence about the optimal aims and methods for glycaemic control in ICU is controversial, and current local protocols guiding practice differ between ICUs, both nationally and internationally. The views of professionals on glycaemic control can influence their practice. Design Cross-sectional, multi-centre, survey based study. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…(2011) recommended setting a higher BG target level to prevent hypoglycaemia because patients can experience hypoglycaemia more than once if the target level of BG is set at 80–110 mg/dl. Previous studies found strong correlation between the frequency of hypoglycaemia and length of ICU confinement and emphasized that medical staff should prioritize minimizing the occurrence of hypoglycaemia in controlling BG in critical care (Fernández‐Méndez et al., 2019; Krinsley et al., 2011). A previous finding that a target level of 180 mg/dl led to lower frequency of hypoglycaemia than that of 120 mg/dl (Jacobi et al., 2012; Lazar et al., 2011) is consistent with this study where the BG target level was set at 100–180 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2011) recommended setting a higher BG target level to prevent hypoglycaemia because patients can experience hypoglycaemia more than once if the target level of BG is set at 80–110 mg/dl. Previous studies found strong correlation between the frequency of hypoglycaemia and length of ICU confinement and emphasized that medical staff should prioritize minimizing the occurrence of hypoglycaemia in controlling BG in critical care (Fernández‐Méndez et al., 2019; Krinsley et al., 2011). A previous finding that a target level of 180 mg/dl led to lower frequency of hypoglycaemia than that of 120 mg/dl (Jacobi et al., 2012; Lazar et al., 2011) is consistent with this study where the BG target level was set at 100–180 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care units develop their own protocols for BG control which differ from one another (Fernández-Méndez et al, 2019;Niven et al, 2015;Orban et al, 2013). Controlling BG safely is fundamental to regulating hyperglycaemia in ICU patients.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Limited studies among ICU professionals have explored the KAP of physicians and nurses regarding glycaemic control. In 2019, Fernandez-Mendez 13 conducted a survey on the views of ICU nurses and physicians on glycaemic control and found that ICU professionals often have different views on glycaemic control, which can affect their clinical practice. They confirmed protocol-practice gaps regarding glycaemic control in the critical care field, but they only focus on professionals' awareness and attitudes, with a lack of investigation on the knowledge and practice behaviour for glycaemic control.…”
Section: Introductionmentioning
confidence: 99%